Magnetic biochar derived from waste palm kernel shell for biodiesel production via sulfonation - Ray Vern, Quah; Yie Hua, Tan; N.M., Mubarak; Jibrail, Kansedo; Mohammad, Khalid; E. C., Abdullah; Mohammad Omar, Abdullah (Elsevier Ltd., 2020)
Due to its environment-friendly and replenishable characteristics, biodiesel has the potential to substitute fossil fuels as an alternative source of energy. Although biodiesel has many benefits to offer, manufacturing biodiesel on an industrial scale is uneconomical as a high cost of feedstock is required. A novel sulfonated and magnetic catalyst synthesised from a palm kernel shell (PMB-SO3H) was first introduced in this study for methyl ester or biodiesel production to reduce capital costs. The wasted palm kernel shell (PKS) biochar impregnated with ferrite Fe3O4 was synthesised with concentrated sulphuric acid through the sulfonation process. The SEM, EDX, FTIR, VSM and TGA characterization of the catalysts were presented. Then, the optimisation of biodiesel synthesis was catalysed by PMB-SO3H via the Response Surface Methodology (RSM). It was found that the maximum biodiesel yield of 90.2% was achieved under these optimum operating conditions: 65 C, 102 min, methanol to oil ratio of 13:1 and the catalyst loading of 3.66 wt%. Overall, PMB-SO3H demonstrated acceptable catalysing capability on its first cycle, which subsequently showed a reduction of the reusability performance after 4 cycles. An important practical implication is that PMB-SO3H can be established as a promising heterogeneous catalyst by incorporating an iron layer which can substantially improve the catalyst separation performance in biodiesel production.